UTP Hostel Energy Saving through Electricity Consumption Control - Mohammad Firdaus Bin Kamaruzaman, Mohammad Firdaus (Universiti Teknologi Petronas, 2010)
The project intends to develop integrated motion detector and light sensor circuit system that is cost and energy-saving. The system is expected to reduce the excessive electricity consumption used at the hostel area. And at the end of this project, the cost of implementing the system will be considered whether it is worth the implementation.